Releasing Captive-Reared Masked Bobwhites for Population Recovery: A Review - Sally A. Gall; William P. Kuvlesky Jr.; George Gee (National Quail Symposium Proceedings, 2017)
Efforts to reestablish the endangered masked bobwhite (Colinus virginianus ridgwayi) to its former historic range have been a primary focus on the Buenos Aires National Wildlife Refuge (BANWR) since it was established in 1986. Prerelease conditioning techniques developed prior to refuge establishment continued to be utilized in an effort to improve postrelease survival of captive-reared masked bobwhite chicks. Foremost among these techniques was the use of wild Texas bobwhite ( C. v. texanus) males as foster parents. Texas foster parents were released with broods from 1985-1996. The efficacy of this technique was evaluated in 1994 using radio telemetry. Results suggested that postrelease survival of chicks was poor. Using an adaptive approach, prerelease protocols were modified over several years in an effort to improve postrelease survival among chicks. Since 1995. released chicks were monitored via radio telemetry and results of the modified releases indicated survival had improved. Though these results are preliminary and this study is ongoing, it appears that our modifications to prerelease conditioning may improve survival rates of captive-reared masked bobwhite chicks. The results of this research project may have implications for captive-reared quail release projects elsewhere.